A spatio-temporal analysis of non-farm enterprise performance in Uganda: 2010-2012. Issue 4 (5th December 2016) - Owoo, Nkechi Srodah
Abstract : Purpose: Recent research into enterprise performance has focussed on the importance of firm proximity to total productivity. Using spatial correlation of firm performance as a proxy for knowledge transfers and diffusion, the purpose of this paper is to examine the evidence for these spatial effects in non-farm enterprise performance in Uganda, across space and time. Design/methodology/approach: The author uses data from the geo-referenced Uganda National Panel Survey from 2010 to 2012, and employs explicit spatial techniques in the analysis of rural non-farm enterprise performance. Spatial autocorrelation of firm performance are used as proxies for knowledge transfers and information flows among enterprises across space and over time. Findings: The study finds evidence of spatial spillover effects across space and time in Uganda. This implies that, as existing studies of developed countries have found, social infrastructure and firm proximity contribute significantly to the performance of rural economies, through information exchange and knowledge transfers. Practical implications: Given the communal nature of rural households in the African setting, knowledge exchange and transfers among neighbouring firms should be encouraged as studies have found they have strong effects on business performance. Additionally, business "leaders" could also be useful in disseminating useful new technologies and applications to neighbouring enterprises in order to boost performance and productivity. Social implications: There should be better targeting of policy interventions to clusters of particularly needy enterprises. Originality/value: To the best of the author's knowledge, this is the first time that spatio-temporal effects of business performance have been explored. While spatial analyses of business performance have been carried out in developed countries, studies using explicit spatial techniques in the developing country setting have been conspicuously absent.